Scaffolded mobile educational game elements for learning memory management / Humaira Amni Hilmi - Hilmi, Humaira Amni (2016)
Operating system (OS) is quite a hard course to be learned by students as it contains a lot of concepts to be understood and it is also an abstract thing to learn which learning it traditionally causes the students to get bored easily. In order to solve this problem, scaffolding technique had been applied in a mobile educational game elements approach that is more engaging and fun which may gain student’s attraction. The research method used was ADDIE which stands for analyze, design, develop, implement and evaluate. This project targeted all Computer Science and Information Technology students that learn OS. The project then was being tested to a total of 30 respondents of computer science and information technology students to test its effectiveness. A survey made had shown a positive result that majority of the respondents choose to learn memory management by using this method as compared to traditional method of learning. Most of the students agreed that the scaffolding technique applied helped them to perform better. This computing project allows students to be more engaged and fun in learning OS. Thus, students can easily apply the concept learned in real world.